The experimental approach in the thought of the philosophers of science (Roger Bacon) and (Francis Bacon) - Shareef, Nadwa Mohammed M. (Al-Adab Journal, 2020)
Human thought is characterized by its continuity, as the latter takes from the former and benefits from it, the real distinction of the philosopher, however stands out in his understanding of the legacy of the former Through a new approach that reflects its independence and innovation and the ability of his approach to put forward new perceptions contribute to the progress of the stage he lives, Arab and Muslim thinkers and scientists have contributed to the modern scientific renaissance of Europe Which is witnessed by the Europeans themselves. The researcher has identified the aim of the research in the experimental approach to the thought of the philosophers of science (Roger Bacon) and (Francis Bacon). With regard to research methodology, the researcher followed the Historical, Descriptive, Analytical, Structural and Comparative Methodology to investigate and analyze data. Among the most prominent results reached by the researcher: Roger Bacon contributed to the rise of science and raised the value of the scientific experiment and the method of induction, Francis Bacon came after him, who rejected Aristotle’s logic known as the organon, he found Aristotle’s logic is based on analogy do not let us discover something new, and it cannot lead to practical control over nature , It is necessary to change it in the experimental method in the modern sense that is starting with sensory experience and careful observations based on induction and scientific experiments and extract results cautiously, he also advised not to separate the mind from experience, because the practical benefit is the most theoretically true .